Necrophagous Diptera Diversity in Samsun During Summer Season - Kokdener, Meltem; Zeybekoğlu, Ünal; Gündüz, Eylem (The Bulletin of Legal Medicine, 2018)
Objective: Necrophagousinsects are colonized cadavers immediately after death. Knowledge of the distribution, biology and behavior of necrophagous insects found at a crime scene can provide important trace about death. The most common application of insect evidence on body is the estimate the minimum time elapsed since death. The objective of this work was to to characterize the assemblage of Diptera, its richness, relative abundance in SamsunProvince, northern Turkey.Materials and Methods: 3 traps (total 6) of 150 g liver were placed at two different natural areas selected from Samsun in June, July and August of 2017 and materials were collected consecutive days. The material was identified according to Spilza’s identification key. In our study, Shannon Wiener and Simpson Diversity Indexes were used to determine the biodiversity index of species in the sample groups of both regions.Results and Conclusion: During the study, 2877 samples of 6 species belonging to 3 different families of Diptera group were collected from two different regions C. vicina, L. sericata, S. argyostoma, S. similis, Ch. albiceps, M. domestica were collected from the baited trap. Significant differences weren’t found between all species that were seen in both regions during the summer season. L. sericata was found to be the most abundant species in two locations during summer seasons. Ch. albiceps were recorded from July 15 to August 15 at OndokuzMayıs University Campus. S. similis were present during August. C. vicina, L. sericata, S. argyostoma were captured at two field during summer.
Keywords: diptera; bait trap; forensic entomology; black sea; samsun